Economists and the powerful : convenient theories, distorted facts, ample rewards - Häring, Norbert (Anthem Press, 2012)
"Economists and the Powerful: Convenient Theories, Distorted Facts, Ample Rewards" explores the workings of the modern global economy - an economy in which competition has been corrupted and power has a ubiquitous influence upon economic behavior. Based on empirical and theoretical studies by distinguished economists from both the past and present day, this book argues that the true workings of capitalism are very different from the popular myths voiced in mainstream economics. Offering a closer look at the history of economic doctrines - as well as how economists are incentivized - "Economists and the Powerful" exposes how, when and why the theme of power was erased from the radar screens of mainstream economic analysis - and the influence this subversive removal has had upon the modern financial world.